Academic Disciplines and Learning Style Preferences of students in graduate level - Chaudhary, Nathu Ram (Journal of Tikapur Multiple Campus, 2014)
Learning styles preference is the vital aspect for teaching learning process. This paper mainly focuses on determining the learning styles of first year graduate students of Tikapur Multiple Campus and examining the relationship between students' Learning style preferences (LSPs) and their faculty as well as gender. The instrument, Index of Learning Styles (ILS), is administered to 112 randomly selected students. As for the data analysis, descriptive statistics portrays the frequencies, percentages; the chi square test is conducted to see whether students' LSPs differ according to faculties and the Crosstabs procedure is conducted to investigate whether the LSPs of the students at TMC differ according to their gender. The results indicate that there is no significant difference between students' LSPs and faculty except understanding dimension. Revealing what the learning style preferences of the first year graduate students of TMC and through this research. Therefore, it will be helpful for further research and pedagogical implications for the teachers to match their teaching with their students.